The current only location-based nodal classification in NSCLC may be inadequate - Maniwa, Tomohiro (Journal of Thoracic Disease, 2019)
We thank Dr. Lee and colleagues for their valuable comments on our article. Dr. Lee discussed the results of three randomized studies evaluating the role of surgery compared to radiation therapy after induction therapy in patients with N2 disease and concluded that there was no difference in overall survival (OS) between the two treatment groups (1-3). However, as per the available national data, a few patients with clinical N2 disease still sometimes receive upfront resection (4,5).